Radioactivity transfer in environment and food - Vosniakos, Fokion K. (Environmental Science and Engineering, Environmental Engineering, 2012)
The book deals with various consequences of major nuclear accidents, such as in 1986 in Chernobyl and in 2011 in Fukushima. The public is extremely interested in learning more about the movements and risks posed by radiation in the environment related to food supply and food safety. Radionuclides are found in air, water, soil and even in us not only after nuclear accidents because they occur also in nature. Every day, we ingest and inhale radionuclides in our air and food and the water. This book provides a solid underpinning of the basic physical-chemistry and biogeochemistry of naturally occurring and anthrop radioactivity. The mechanisms of radioactive element transfer in the atmosphere, tropospheric and stratospheric diffusion of radioactivity, environmental contamination from accidents and the impact of atmospheric pollution on the food chain, soil and plants, are analyzed and the analytical methods are illustrated. The question of natural radioactivity concentration in building materials is addressed too. While the book contains many case studies and data for Greece, it is of general value. It contributes to the development of international environmentally safe standards and economically reasonable standard regulations based on justified radiological, social and economical legislation concepts.